2022
DOI: 10.3390/ijerph19148791
|View full text |Cite
|
Sign up to set email alerts
|

Research on Determining the Critical Influencing Factors of Carbon Emission Integrating GRA with an Improved STIRPAT Model: Taking the Yangtze River Delta as an Example

Abstract: Driven by China’s peak carbon emissions and carbon neutrality goals, each region should choose a suitable local implementation path according to local conditions, so it is of great significance to mine and analyze the critical influencing factors of regional carbon emissions. Therefore, this paper integrates grey relation analysis (GRA) and an improved STIRPAT model and selects the Yangtze River Delta region of China as the research object to analyze the factors affecting carbon emissions in four provinces in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The used models and methods of this study are equally applicable to other regions and researches and/or investigations. For example, an improved STIRPAT model was adopted to explore the critical influencing factors of carbon emission in the Yangtze River Delta [ 67 ], whereas an extended STIRPAT model was employed to analyze the multivariate driving factors of carbon emissions from energy consumption in Xinjiang Province [ 95 ] and the other provincial household carbon emissions in China [ 96 ]. Other research reports employing similar models and methods are found in the web search too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The used models and methods of this study are equally applicable to other regions and researches and/or investigations. For example, an improved STIRPAT model was adopted to explore the critical influencing factors of carbon emission in the Yangtze River Delta [ 67 ], whereas an extended STIRPAT model was employed to analyze the multivariate driving factors of carbon emissions from energy consumption in Xinjiang Province [ 95 ] and the other provincial household carbon emissions in China [ 96 ]. Other research reports employing similar models and methods are found in the web search too.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon sink is the process, activity, or mechanism of absorbing carbon dioxide in the atmosphere through afforestation, vegetation restoration and other measures, so as to reduce concentration of greenhouse gas in the atmosphere [ 62 , 63 , 64 , 65 ]. It is an important part of the ecosystems and an important way to achieve the regional carbon neutrality [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. In the long-term grain crop planting process, grain crop production and forest coverage had a significant effect on carbon emission absorption [ 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…The STIRPAT model, an important tool for environmental analysis, is derived from the IPAT environmental pressure equation proposed by Ehrlich et al and is widely used to analyze the non-proportional impact of human driving factors on the environment (Ehrlich and Holdren, 1971). In this paper, referring to the practices of Guo et al (2022b), Zhang et al (2023b), Peng et al (2023), andLiu et al (2023), a nonlinear STIRPAT model with multiple independent variables is constructed, and its basic formula is as follows:…”
Section: Analysis On Influencing Factors Of Agricultural Carbon Emiss...mentioning
confidence: 99%
“…The first is the Logarithmic Mean Division Index (LMDI) decomposition model, lauded for its distinct analysis pathway, lack of residual, and excellent zero-value processing capacity; hence, it is extensively employed in carbon emission driver decomposition research across multiple fields [14]. The second model is the STIRPAT model, appreciated for its scalability and stochasticity, which has found broad application in energy carbon emission prediction and assessment research [15]. The third method is the Grey Relational Analysis (GRA), a tool used within grey system theory to measure the similarity or heterogeneity among various factors [16].…”
Section: Literature Reviewmentioning
confidence: 99%